Kinetics of RH, RU, and IR dissolution during the Sulphuric Acid Pressure Leaching of First Stage Leach Residue - Dorfling, C.; Akdogan, G.; Bradshaw, S; Eksteen, Jacques (New Concept Information Systems Pvt Ltd., 2012)
Experimental work was performed using a bench scale autoclave to evaluate the effects that leaching temperature, pressure, initial acid concentration, and the solid to liquid ratio have on the behaviour of base metals and platinum group metals in a high-pressure sulphuric acid oxygen leaching system. The concentrations of metals in the leach solution were measured over time at different leaching conditions. At the conditions investigated, the initial acid concentration had the largest influence on the copper leaching kinetics, while the leaching rates of the other precious metals (OPMs: rhodium, ruthenium, and iridium) were highly dependent on the leaching temperature. A set of chemical reactions that can be used to describe the leaching chemistry was proposed, and the associated reaction kinetics were quantified. As a first estimation, the rate expressions were considered first order, and the rate constants were determined using the method of least squares, considering the experimental and predicted concentrations obtained for the different leaching conditions. Of the OPM compounds, the sulphides showed the fastest dissolution rate, followed by OPM alloys, and finally the OPM oxides. During the initial leaching stages, base metals and OPMs competed for the available dissolved oxygen, with oxygen being preferentially used for copper leaching. Precipitation of OPMs during the initial leaching stages can be ascribed to copper and nickel dissolution according to exchange reactions between dissolved OPMs and copper present as digenite or nickel present as polydymite. Control of the autoclave residence time is of particular importance to enhance the selectivity of this leaching step, given the dependence of the PGM leaching rates on the extent of copper dissolution.